Ergonomic Analysis in Optimizing Science Learning: Physical Environment Impact on Academic Performance - Erna Lestari Rambe; Khairul Zikri; Dedi Nofrizal (CV. INSPIRETECH GLOBAL INSIGHT, 2026)
Purpose of the study: This research investigates the relationship between classroom ergonomic conditions and science learning outcomes in elementary schools, aiming to identify optimal physical environmental factors that enhance student academic performance and teacher effectiveness in science education. Materials and methods: A quantitative cross-sectional study was conducted involving 450 students and 45 teachers from 15 elementary schools in Pekanbaru City, Indonesia. Data collection utilized structured questionnaires measuring classroom design adequacy, ergonomic comfort levels, and their perceived impact on science learning. Statistical analysis was performed using SPSS version 29.0, employing descriptive statistics, correlation analysis, and multiple regression modeling. Results: Significant positive correlations were found between ergonomic classroom conditions and science learning outcomes (r = 0.742, p < 0.001). Students in ergonomically optimized environments demonstrated 23.5% higher science achievement scores compared to those in suboptimal conditions. Teacher satisfaction with classroom ergonomics showed strong correlation with instructional effectiveness (r = 0.681, p < 0.001). Key ergonomic factors influencing learning included appropriate furniture sizing (β = 0.312), adequate lighting conditions (β = 0.287), and optimal temperature control (β = 0.245). Conclusions: Ergonomic optimization of elementary school classrooms significantly enhances science learning outcomes. Implementation of evidence-based ergonomic principles in classroom design can substantially improve both student academic performance and teacher instructional effectiveness. These findings support the integration of ergonomic considerations as essential components in educational facility planning and science curriculum delivery.